Electric field controlled type-I and type-II conversion of BP/SnS van der Waals heterostructure. (25th May 2021) - Chen, Jia-Le; Wang, Xin-Xin; Shi, Li-Jie
Abstract: Type-I heterostructure, in which electrons and holes are confined in same region, is widely used in light emitting diodes and semiconductor lasers. Type-II heterostructure is widely used in photovoltaic devices because of its excellent spatial separation property of electrons and holes. Can we integrate photovoltaic, photoelectric properties with luminescent property in one device? Here we report a van der Waals heterostructure formed by black phosphorus (BP) and SnS monolayers. It is expected to realize these functions in one device. By first-principles methods, the structural stability, electronic properties and optical properties are investigated. It was found that the BP/SnS bilayer is type-II heterostructure with an indirect bandgap of 0.56 eV. The p -like character of the band edge in BP/SnS vdW heterostructure makes it to be an excellent optoelectronic material. The type-II stability of the system can be improved by applying a negative electric field. However, when the positive electric field is bigger than 0.1 V Å −1, the system begins to transform from type-II to type I. Therefore, by adding a gate voltage the bandgap and band alignment of this system can be controlled. The photovoltaic and photoelectric properties can be integrated in one device based on this heterostructure.